2019
DOI: 10.22161/ijels.4.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pipe-borne water supply in the Buea Municipality: Challenges and way forward

Abstract: A growing quest in the mind of man today is to establish a balance equation between his activities and the available freshwater. Trillion of dollars have been spent worldwide to reduce water shortages, but governments and stakeholders ubiquitously have failed to empower the city dwellers and to ambush the challenges to pipe borne water supply. In many parts of developing countries including Cameroon, population growth , urbanization and water demands are rising rapidly, whereas water availability, quality, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…This was followed by community taps, springs and wells. This was in contrast with the study of Baba et al, (2019), who noted that pipe borne water was the major water source in the Buea Municipality. Further investigations showed that most of the individuals cannot boost of 20 litres of water daily and many of them traveled over 1km distance in search of portable water.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This was followed by community taps, springs and wells. This was in contrast with the study of Baba et al, (2019), who noted that pipe borne water was the major water source in the Buea Municipality. Further investigations showed that most of the individuals cannot boost of 20 litres of water daily and many of them traveled over 1km distance in search of portable water.…”
Section: Discussioncontrasting
confidence: 86%
“…These findings were in line with that of WHO (2012) who in assessing water quality and the associated health risks in the city of Yaounde, noted that 50% of the diseases in the area were airborne diseases caused be inadequate portable water. Baba et al (2019) also noted that poor sanitation was also one of the most devastating effects of water shortages worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te respondents believed that their closeness to water source is signifcant to the pattern of their daily water demand as shown in Table 2. Te authors of [51][52][53] had reported that one of the factors that infuence household water use is the distance from the source of water. When respondents have short distance to cover in getting potable water for home use, there is possibility that more volume of water will be used in homes.…”
Section: Closeness To Water Source (Denoted As L)mentioning
confidence: 99%